ANALYSIS OF MASAMO CATFISH MARKETING BY ANALYTICAL APPROACH AT FARMER GROUP “SUMBER LANCAR”, BLIMBING, MALANG CITY - Abidin, Zainal; Handayani, Wahyu; Fattah, Mochammad (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2016)
Masamo as new variety of catfish cultivated by the farmer group "Sumber Lancar" in Blimbing, Malang currently has a lot of demand due to increasing consumers who like to eat fish to meet the need for protein for the body. Increasing of Masamo catfish demand followed by production and marketing efforts. This study wants to know whether the marketing efficient. Therefore, this study uses analytical approach approach in order to identify institutional and channel of Masamo Catfish marketing performed by that Group, analyze marketing functions and its marketing efficiency. Data were collected by interview, observation and literatur study. Based on the research, the marketing agencies involved in Masamo catfish marketing consist of fish producers and traders. The marketing has four channels, in which channel I is an indirect marketing channel, while the channel II-IV is a direct marketing channel. The marketing functions are mostly done by middlemen rather than farmers. Masamo catfish marketing are generally quite efficient because short marketing channels, low marketing margins, marketing costs share by 19.6%, while the profit share amounted to 80.4%; the farmer’share is still greater than marketing margin. Suggestions for fish farmer to increase production capacity.